Från privat viljeyttring till offentlig registrering: Om möjligheterna att inrätta ett offentligt testamentsregister i ljuset av den danska rättsordningen - Johansson,Lowa (2025)
This thesis aimed to examine whether a public register of wills should be introduced in Swedish Law or not. The study sought to identify needs within the Swedish legal system and the advantages and disadvantages of establishing such a register, which were then addressed and analyzed. Primarily, the legal certainty regarding whether a testator’s final wish is made known has been problematized. Throughout the study, the Swedish conditions have been compared to the Danish legal system and its Central Register of Wills from 1932. The comparative narrative has provided a deeper understanding of the different legal choices despite the common Nordic legal culture, thus opening a discussion about legal inspiration. By using legal historical, legal dogmatic, and comparative methods, the study has mapped the development of the law of wills, commented on current Swedish and Danish law, and provided an insight into the fragmented political discussion and motives behind the different choices in the legal systems. In the analysis, it is clarified that there is not any particular reason as to why an introduction should not take place. A public register of wills included benefits such as strengthened protection for preservation of the ultimate will, simplified estate inventories and a more systematic organization. Nevertheless, objections about the historical absence and organizational conditions could be dismissed. The Danish Central Register of Wills, on the other hand, could only serve as limited inspiration. No direct transfer of the Danish register system could be advocated, due to major structural differences in how the courts and authority organizations are divided. What the register in Danmark however could do is to provide guidance regarding digitalization and practically illustrate the possible security advantages to be gained.
Keywords: familjerätt; rättshistoria; testamentsrätt; komparativ; danmark; testamentsregister; testamente; ärvdabalk; arvelov